BP's pipeline strategy : unlocking the value of Azerbaijan's offshore oil fields - Hutchins, Spencer; Dadashev, Farid; Elias, Jaan; Grasso, Tom ([London] : SAGE, 2016)
In Azerbaijan, observers had hailed it as the 'contract of the century.' In September of 1994, the Azerbaijani government signed a Production Sharing Agreement (PSA) with a consortium of eleven oil companies, collectively known as the Azerbaijan International Oil Company (AIOC). The PSA spelled out the plans to develop a Caspian Sea oil field called Azeri-Chirag-Guneshli (ACG), 37 miles off the shore of Baku, Azerbaijan's capital. The members of the AIOC would invest over $15 billion dollars in this project, making it one of the largest non-military capital investments in the world. For Azerbaijan, the development of ACG promised to transform the economy and reestablish the country as a centre of the oil industry. This case study examines this topic.
Originally Published in: Hutchins, S., Dadashey, F., Elias, J., & Grasso, T. (2008). BP's Pipeline Strategy: Unlocking the Value of Azerbaijan's Offshore Oil Fields. 06-020. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; British Petroleum Company; Strategic planning -- Case studies; International business enterprises -- Management -- Case studies; Oil industries -- Azerbaijan -- Case studies; Petroleum industry and trade -- Azerbaijan -- Case studies; Negotiation in business -- Case studies